Characterization of Titanium dioxide (TiO2) Nanoparticles Biosynthesized using Leuconostoc spp. Isolated from Cow’s Raw Milk: Characterization of (TiO2 ) Nanoparticles - Susan Abdul Raheem Hasan; Jehan Abdul Sattar Salman; Sawsan Sajid Al-Jubori (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
Nanotechnology is a continually expanding field for its uses and applications in multiple areas i.e. medicine, science, and engineering. Biosynthesis is straightforward, less-toxicity, and cost-effective technology. TiO2 NPs biosynthesis has attained consideration in recent decades. In this study, probiotic bacteria were isolated from cow’s raw milk samples, and then were identified by using the Vitek2 system; as Leuconostoc spp. included Leuconostoc mesenteroides subsp. mesenteroides (Leu.1), Leuconostoc mesenteroides subsp. cremoris (Leu.4), and Leuconostoc pseudomesenteroides (Leu.14). All Leuconostoc spp. isolates showed an ability for TiO2 NPs bio-production, after being incubated at anaerobic conditions (30 o C/ 24 h) in DeMan Regosa and Sharpe (MRS) broth medium. The biosynthesized TiO2 nanoparticles were characterized using the following apparatuses: UV-Vis spectroscopy, X-ray diffraction (XRD) apparatus, Atomic Force Microscopy (AFM), Fourier Transform Infrared Spectroscopy (FTIR), Field Emission Scanning Electron Microscopy (FE-SEM) in addition to Energy Dispersive X-ray analysis (EDX) spectra. The characterized biosynthesized TiO2 NPs were spherical-shaped, nanostructure anatase crystals with an average size range of 53.35-59.41 nm. The UV absorption spectrum was observed at the wavelength 344-248 nm; the topography AFM 2D and 3D images result showed the height and roughness of biosynthesized TiO2 NPs that were in the range of 1.137-18.88 nm. Absorption peaks in the FTIR spectra were located in a region typical of TiO2 NPs, and biosynthesized TiO2 nanoparticles’ main IR topographies (408.21- 445.80) cm-1 belonged to anatase Titania (Ti-O-Ti) bridge.